2016
DOI: 10.2337/dcs15-3005
|View full text |Cite
|
Sign up to set email alerts
|

Positioning SGLT2 Inhibitors/Incretin-Based Therapies in the Treatment Algorithm

Abstract: S154Diabetes Care Volume 39, Supplement 2, August 2016 SGLT2 THERAPYsensitizer (6,7). GLP-1 is part of the physiological system signaling satiety (8,9), reduces food intake and promotes weight loss in humans (10), and delays gastric emptying (11). Early studies showed that continuous subcutaneous GLP-1 infusion effectively lowered fasting and postprandial glucose levels and promoted weight loss in patients with T2DM (12). However, endogenous human GLP-1 has a short half-life (2-3 min) due to breakdown in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 108 publications
(38 reference statements)
0
35
0
Order By: Relevance
“…Sulfonylureas can also have negative lipid effects [71, 72, 73, 74]. The SGLT2 inhibitors can lower TG and raise HDL but may also raise LDL-C levels slightly; in the case of empagliflozin, this has been shown to be mainly due to hemoconcentration [75, 76]. Importantly, recent studies have demonstrated positive CV outcomes with several antidiabetic agents, including pioglitazone [77], empagliflozin [78], liraglutide [79], and semaglutide [80] without a clear relationship to effects on lipid levels.…”
Section: Current Treatment Guidelinesmentioning
confidence: 99%
“…Sulfonylureas can also have negative lipid effects [71, 72, 73, 74]. The SGLT2 inhibitors can lower TG and raise HDL but may also raise LDL-C levels slightly; in the case of empagliflozin, this has been shown to be mainly due to hemoconcentration [75, 76]. Importantly, recent studies have demonstrated positive CV outcomes with several antidiabetic agents, including pioglitazone [77], empagliflozin [78], liraglutide [79], and semaglutide [80] without a clear relationship to effects on lipid levels.…”
Section: Current Treatment Guidelinesmentioning
confidence: 99%
“…Metformin has a clear advantage over sulfonylureas, which lead to a weight gain of 2-3 kg. However, compared with the glucose-lowering and weightreducing effects of glucagon-like peptide-1 (GLP-1) analogues and sodium−glucose cotransporter 2 (SGLT2) inhibitors, metformin appears not to provide any additional weight benefit [10].…”
mentioning
confidence: 99%
“…Caution may be used in individuals with a history of HF based on the selected DPP4i, paying attention to signs and symptoms of heart failure during therapy. In these individuals, concomitant use of a sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor may be considered also because of the reduced risk of HF and CV protection …”
Section: Discussionmentioning
confidence: 99%